Bean research and production needs in Malawi - Tinsley, R.L. (National Bean Programme, 1990)
The two days of discussion highlighted several areas of need in developing a Bean Production Improvement Programme. The most critical need appeared to be an evaluation of seed availability and the use of new seed varieties within existing mixtures. Other ideas included intensifying the maize-bean intercropping and mid-season plantings. Also considered was the growing of beans on the flu- cured tobacco estates and relayed into sugarcane ratoons. There was concern about possible duplication of effort with the Maize Commodity Team's work on spatial arrangements of maize bean intercrops. (AS)